Memory, Nootropics and Ayurveda- A Critical Appraisal: Life Sciences-Ayurveda - Verma, Jitesh; Rathi, Renu; Ibamedabha; Anamika; Rathie, Bharat; Pandey, VB (International Journal of Life Science and Pharma Research, 2023)
Memory is an essential function of our cognition that helps us to remember events, learn lessons and preserve emotions; to live each day with new learning and optimum behavior. There have been talks on using safe nootropic drugs to enhance Memory in healthy patients with memory disorders. The ancient sages of Ayurveda and Vedic civilizations advocate learning and memorizing many hymns and verses by their pupils. It leads to the discovery of the cognition and memory enhancing drugs known as Medhya Rasayana. Ayurveda possesses a treasure of Medhya Rasayana, known as nootropics. This review aims to elaborate on and explain the Ayurvedic concept of memory and nootropics about the contemporary concept. Online research databases like DHARA, Ayush Research Portal, Pubmed, Google Scholar, etc., were searched for relevant research articles by applying adequate keywords. Ayurvedic concepts of Buddhi, acquisition of knowledge, Medha, and Medhya Rasayana were reviewed from Ayurvedic classics. This paper discusses the contemporary concept of memory along with its classification, mechanisms of production, and probable mode of its enhancement. The well-described Ayurvedic concept of the cognitive process and Medha and Pragya (intellect) have been analyzed, elaborated, and explained as per contemporary knowledge. A few Medhya drugs like Brahmi (Bacopa monnieri), Mandookaparni (Centella asiatica), Shankhpushpi (Convolvulus pluricaulis), and Vacha (Acorus calamus) are analyzed for their properties explained in Ayurveda and their neuropharmacological activities in the light of recent experimental and clinical studies. The probable two groups based upon the mode of action of Medhya drugs- one which promotes Dhriti and the other which promotes Medha (mainly Dhi & Smriti) are also discussed. In conclusion, memory enhancement in healthy and pathological states is requisite in today's competitive world. With its vast treasure of Medhya drugs, Ayurveda can greatly help in this field